The Legal Status of Minor Testator’s Parents Deprived of Parental Authority in Intestate Succession. Some Remarks on the Solutions in Polish, Russian, and Italian Law - Witczak, Hanna (Review of European and Comparative Law, 2021)
The legal situation of minor testator’s parents in intestate succession poses a significant legal and social problem. In Polish law, parents who have been deprived of parental authority continue to enjoy their civil-law status; in other words, they maintain the right to inherit from their child under statute. Meanwhile, the reasons for which the court applied the strictest possible “sanction” in the form of deprivation of authority of parents who, in exercising their rights under parental authority, seriously violated the child’s interest or grossly neglected parental obligations, which is noticeable even to an ordinary bystander, seem to be sufficient “proof” that family ties, which are decisive for the statutory title to inherit, do not exist. If these ties are severed or seriously disrupted, the consequences should be seen in all areas of life. Simply put, persons who deliberately break apart the family should not enjoy the advantages that the law provides for testator’s closest relatives. In such a case, to consider the effect of deprivation of parental authority by “releasing” its holders from any obligation towards the child may not be considered a sufficient civil sanction, especially given that in the vast majority of cases, the reason for such deprivation is gross neglect of parental duties by one or both parents. The consequences of this type of negligence should also, if not primarily, consist in the deprivation of pecuniary benefits that the parents of a minor could enjoy after his or her death. The current legal solutions governing this area undoubtedly need to be revised. Such imperfect normative solutions adopted in Polish law prove the need to propose de lege ferenda recommendations. In this context, it is worthwhile to have a look at the normative solutions adopted in foreign legal systems and whether they can be grafted on Polish law. The reference to the Russian and Italian legal systems seems particularly recommendable due to the fact that their normative solutions directly allude to the institution of deprivation of parental authority in the context of admissibility of the title to inherit.